2011
DOI: 10.1152/ajpendo.00699.2010
|View full text |Cite
|
Sign up to set email alerts
|

Restoring HSP70 deficiencies improves glucose tolerance in diabetic monkeys

Abstract: We evaluated heat shock protein 70 (HSP70) changes in diabetes mellitus (DM) in a nonhuman primate model. To this end, two studies were conducted in DM vervet monkeys. 1) Normal control and streptozotocin-induced DM monkeys (Stz-DM) that were differentiated into moderately or poorly controlled DM by judicious insulin administration were evaluated. Liver was collected at 4,8,12,16, and 20 wk after streptozotocin, exposed to ex vivo heat shock at 42°C, and immunoblotted for heat shock factor 1 (HSF1), HSP70, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 50 publications
4
58
0
Order By: Relevance
“…Heat stress response includes activation of the heat shock transcription factor (HSF) and increased expression of heat shock proteins (HSPs) (Collier et al, 2008). Intriguing work demonstrates that extracellular HSP70 concentrations also increase during heat stress (Kavanagh et al, 2011;Gaughan et al, 2013). Therefore, we need to further investigate serum HSF and HSPs.…”
Section: Introductionmentioning
confidence: 99%
“…Heat stress response includes activation of the heat shock transcription factor (HSF) and increased expression of heat shock proteins (HSPs) (Collier et al, 2008). Intriguing work demonstrates that extracellular HSP70 concentrations also increase during heat stress (Kavanagh et al, 2011;Gaughan et al, 2013). Therefore, we need to further investigate serum HSF and HSPs.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive literature relates abnormalities of HSP's and type 2 diabetes (Nakhjavani et al 2011;Nakhjavani et al 2010;Kavanagh et al 2011). Recent studies have shown the role of these molecules in the pathogenesis of diabetic nephropathy (Calabrese et al 2007;Buraczynska et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, poor HSP70 mRNA expression is found in diabetic humans and correlates with reduced mitochondrial enzyme activity (Bruce et al, 2003), increased JNK activity (Chung et al, 2008) and the degree of insulin resistance (Kurucz et al, 2002). Evidence from animal models of DM also supports this finding at the protein level (Atalay et al, 2004;Kavanagh et al, 2011). Given the profound impact of HSP on stress kinases and mitochondrial integrity, it is conceivable that reduced HSP expression might have unfettered the deleterious inflammatory signaling and redox homeostasis which accelerate the development of insulin resistance.…”
Section: Hsp Enhances Mitochondrial Functionmentioning
confidence: 95%
“…Nevertheless, there appear to be some compounds such as geranylgeranyl acetone (GGA) that directly modulate HSP70. GGA is currently the leading antiulcer drug in Japan (Ushijima et al, 2005) and has been shown to be neuroprotective against cerebral ischemia, polyQ toxicity (Sajjad et al, 2010) and recently in a diabetic monkey model to attenuate insulin resistance (Kavanagh et al, 2011) via the induction of HSP70. As many of the other HSR inducers or co-inducers, the HSP induction mechanism of GGA is not elucidated but has been suggested via dissociation of HSF-1 from HSP70 by competitively interacting with HSP70 C-terminal peptide-binding domain, which is the HSF-1 binding sites during HSP70-HSF-1 negative feedback (Otaka et al, 2007).…”
Section: Hsp70: Potent "Cytoprotectant"mentioning
confidence: 99%
See 1 more Smart Citation